The economic impacts of the UK-Vietnam free trade agreement (UKVFTA) on Vietnam’s electronics industry - Hoang, Cuu Long; Nguyen, Thi Thu Phuong (Journal of Finance - Marketing Research, 2023)
This study analyses the economic impacts of the UK-Vietnam Free Trade Agreement (UKVFTA) on Vietnam’s electronics industry (EI) after the UKVFTA had been signed for the period from 2017 to 2021. The TSI, GL/IIT, and CTB indexes were employed to analyze the electronics items traded between the UK and Vietnam. The results showed that Vietnam’s electronics industry after the UKVFTA does not result in a significant increase. This agreement still ensures that trade flows smoothly as possible leading to economic development between Vietnam and the UK, after Brexit, especially in the context of the Covid-19 crisis. Therefore, the UKVFTA would still have a crucial role to play in Vietnam’s electronics industry and the trade structure of both countries in general. In addition, Vietnam should take measures to improve its competitive position in the EI, boost trade between the two countries, and raise the welfare of Vietnam in the future.